2020
DOI: 10.1111/aji.13221
|View full text |Cite
|
Sign up to set email alerts
|

Mild steel and stainless steel welding fumes elicit pro‐inflammatory and pro‐oxidant effects in first trimester trophoblast cells

Abstract: Problem As more women join the skilled‐trade workforce, the effects of workplace exposures on pregnancy need to be explored. This study aims to identify the effects of mild steel and stainless steel welding fume exposures on cultured placental trophoblast cells. Method of study Welding fumes (mild steel and stainless steel) were generously donated by Lincoln Electric. Electron microscopy was used to characterize welding fume particle size and the ability of particles to enter extravillous trophoblast cells (HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…It should be noted that particles with a diameter of less than 0.5 mm might deposit in the upper respiratory tract. The degree and location of particle deposition depend on several factors, such as particle size, density, and shape, the anatomy of the airways, and the breathing pattern of the individual (10). According to Lorenzo G. , the majority of the mass contribution came from particles with cut-off diameters between 0.1 and 1.0 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that particles with a diameter of less than 0.5 mm might deposit in the upper respiratory tract. The degree and location of particle deposition depend on several factors, such as particle size, density, and shape, the anatomy of the airways, and the breathing pattern of the individual (10). According to Lorenzo G. , the majority of the mass contribution came from particles with cut-off diameters between 0.1 and 1.0 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Welding fume has been classi ed as ''possibly carcinogenic'' by the International Agency for Research on Cancer (IARC) (1). Moreover, Respiratory irritation, occupational asthma, bronchitis, chemical pneumonitis, metal fume fever, neurological effects and dysfunction of the male reproductive system and a potential rise in lung cancer are the risks that a huge number of welders face, according to epidemiological studies (9,10). Other investigations have demonstrated welding fumes contain speci c metals that produce reactive oxygen species (ROS) such as hydroxyl radicals (•OH), superoxide anion (O2), singlet oxygen (1O2) and hydrogen peroxide (H2O2) (11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a retrospective study found a synergistic effect of smoking and welding fumes on lung cancer ( 19 ). Studies have shown that soluble Cr(VI) and Mn in welding fumes are associated with acute cellular and genotoxic effects in vitro , and insoluble ferric oxide has long-term effects on the human body and has potential lung cancer risk ( 20 , 21 ). In this study, the concentration of welding fumes and the major metal ions Cr, Mn, Fe, and Ni were detected in the individual and fixed spot of the welders.…”
Section: Discussionmentioning
confidence: 99%